Educational determinants of return migration of Poles - Organiściak-Krzykowska, Anna; Machnis-Walasek, Joanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
Migration is a very important socio-economic issue in the contemporary world. One of the interesting and pertinent research problems worth considering concerns the scale and nature of migration from countries which entered the European Union in 2004. The enlargement of the EU led to a significant increase in the number of part-time/temporary migrants. According to statistical data, the number of Polish emigrants increased nearly four times from 451 thousand in 2002 to 1720 thousand in 2012. In the context of global economic crisis, there appeared a number of questions about the international migration and return migration of Poles. This paper describes educational determinants of return migration of Poles. The main aim of paper were diagnosis and evaluation of the determinants of higher educated Poles’ migration and remigration. Based on empirical research, the paper aims to establish whether Polish migrants’ jobs are commensurate with their qualifications. There is answer the question whether migrant`s work enriched their social capital in the new knowledge and skills, or rather caused deskilling and brain waste.